Penyuluhan Peran Kerjasama dalam Organisasi bagi BEM dan UKM di Universitas Widya Mataram - Artha, Bhenu; Asri, Cahya Purnama; Sari, Utami Tunjung; Khairi, Ardhi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This community service activity provides counseling to BEM and UKM management in the UWM environment which aims to provide additional understanding and knowledge about the relationship between organizational cooperation, intellectual capital and human capital, therefore BEM and UKM UWM administrators can run the organization better. This community service activity is carried out using lecture, demonstration, and question and answer methods. The benefits that can be obtained by participants from this community service activity include increasing the knowledge, understanding, and experience of UWM BEM and UKM administrators regarding the relationship between organizational cooperation, intellectual capital and human capital